Public enemy number two - Horowitz, Anthony (Walker London, 1997)
Framed for a jewel robbery, quick-thinking young Nick Diamond finds himself sharing a prison cell with Johnny Powers, Public Enemy Number One. His only chance of rescuing the situation is to nail the Fence, the country's number one criminal. But first Nick has to get out of jail. Suggested level: primary, intermediate, junior secondary